1977
DOI: 10.1177/004051757704701008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Cotton Fiber Properties to Yarn Tenacity

Abstract: Fiber tenacity, elongation, length, fineness, and color were measured for 5 Gossypium barbadense L. and 37 G. hirsutum L. fiber samples. These samples were spun into 12- and 27-tex yarns on a ring system and into 27-tex yarns on an open-end system; yarn tenacity was determined. Fiber tenacity and length were positively correlated with yarn tenacity. No correlations of fiber fineness with tenacity of 27-tex yarns were detected. A substantial portion of the variation in 27-tex yarn tenacity was attributable to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 3 publications
3
34
0
Order By: Relevance
“…Similar anomalies, however, can be seen in the regressions quoted by other authors (Parker, 1982;Ramey, Lawson & Worley, 1977;El Hattab, El-Shaer & Samra, 1972).…”
Section: Resultssupporting
confidence: 87%
“…Similar anomalies, however, can be seen in the regressions quoted by other authors (Parker, 1982;Ramey, Lawson & Worley, 1977;El Hattab, El-Shaer & Samra, 1972).…”
Section: Resultssupporting
confidence: 87%
“…Our statistical curve estimation analysis showed that the relationship between fiber properties and yarn elongation was not very linear and so the prediction power of our regression model was not very high. Some other studies [2][3][4][5]21] have shown that there is a contrary relationship between fiber strength and fiber elongation. One possible explanation of the negative sign for fiber elongation, similar to the prediction of yarn tenacity, is that autocorrelation (between fiber strength and fiber elongation) could cause instability in the estimation coefficients.…”
Section: Influence Of Fiber Properties On Yarn Elongationmentioning
confidence: 99%
“…Testing with a High Volume Instrument (HVI) (Uster Technologies AG, Uster, Switzerland) (Schleth et al 2007) is standard practice to determine these fibre attributes in many production regions, and these properties are used to establish the value of cotton fibre (USDA 2005). HVI properties explain much but not all of the variation in yarn strength, and significant work has been conducted into understanding the relative contribution of fibre properties (El Sourady et al 1974;Ureyen and Kadoglu 2006) and how these properties relate to yarn performance, through the development of fibre quality indices (Hunter 2004) or modelling techniques (Ramey et al 1977;Zurek et al 1987;Cheng and Adams 1995). There remain opportunities to include fibre quality measurements that may better explain yarn strength, for example by employing alternative attributes for, among others, the still commonly used micronaire measure.…”
Section: Introductionmentioning
confidence: 99%